Indigenous education rights: the Malaysian case - Rosnon, Mohd Roslan; Abu Talib, Mansor (Management Academic Research Society, 2019)
United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) was created to give Indigenous peoples the right to determine their own educational system. In article 14 it is stated that, Indigenous peoples have the right to establish and control their educational systems and institutions, providing education in their own languages; in a manner appropriate to their cultural methods of teaching and learning. Ever since the 61 years of independence, Orang Asli has never been neglected or excluded from the government’s planning in ensuring their education development. Therefore, this paper relied on the qualitative approach using secondary data. This paper reviews the current and the past reports from 1995 until 2015 that reflect the shifts in government policy of Indigenous education in Malaysia. The data were then analysed using thematic analysis. Evidences from a range of reports, have been utilised to shed light on why Indigenous peoples’ educational disadvantage persists, despite extensive government and community effort and resources. This paper also highlights and recommends the self-determination, equity and recognition for Orang Asli education system. Furthermore, Orang Asli have the best knowledge of their culture and curriculum needs and the most appropriate approach, which enable them to cater for their own particular circumstances and create a successful outcome in the development of Indigenous education policy.